Design of Graphene- and Polyaniline-Containing Functional Polymer Hydrogel as a New Adsorbent for Removal of Chromium (VI) Ions - Chin, Jae-Seo (Polymers (Basel), 2016)
Hydrogels find applications in various fields, and the ever-growing spectrum of available monomers, crosslinking, and nanotechnologies widen the application of polymer hydrogels. Herein, we describe the preparation of a new graphene (G)- and polyaniline (PANI)-containing functional polymer gel (G/PANI/FG) through a facile crosslinking copolymerization approach. Several characterization techniques such as field-emission scanning electron microscopy, Fourier-transform infrared, and X-ray photoelectron spectroscopy were employed to understand the physicochemical characteristics of the G/PANI/FG. The new G/PANI/FG was used as an adsorbent for chromium (VI) and exhibited the highest Cr (VI) removal efficiency (~97%). The inclusion of G and PANI in the gel results in high surface area, 3D porous structure, and Cr (VI)-chelating amine sites, which enhanced the Cr (VI) removal efficiency and thermal stability of the gel adsorbent. The results of our study revealed that G/PANI/FG is suited for the removal of Cr (VI) from aqueous solution.